“It’s the teachers’ fault”: Personalizing the gaps with school-based value-added measures - Garver, Rachel (Education Policy Analysis Archives, 2022)
Efforts to measure teacher effectiveness have intensified across the globe over the last two decades. In the United States, educational reforms that attempt to further educational equity have concentrated on aspects of schooling, such as teacher quality, that are more easily manipulated and monitored than powerful out-of-school factors, such as economic and racial segregation. Teachers in high-poverty, racially segregated schools are subject to strengthened accountability policies that seek to precisely evaluate teachers as they face student needs that research shows are difficult to address fully within the classroom. How does this disconnect between causes and remedies shape equity work in high-poverty, segregated schools? I examine how the administration at a public middle school in the United States held teachers independently responsible for the comparative performance of each student subgroup. This project of “personalizing the gaps” involved developing a theory of action that linked performance gaps to classroom practice and creating a value-added data set that traced the growth of each subgroup in teachers’ classrooms. In turn, teachers ‘personalized the gaps’ when under direct administrative supervision and at other times resisted by proposing alternative explanations for performance gaps or questioning the validity of the administration’s data practices.